Pengembangan Sistem Layanan Praktikum Berbasis Web dengan Pendekatan Model Incremental - Rio Rinaldi; Yusrizal Hakim (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2026)
This study designs a web-based practicum management information system for the Computer Science Program at UIN North Sumatra. It addresses the inefficiencies of manual recording, which are prone to data loss and administrative delays. Developed using the Incremental model and PIECES analysis with PHP, MySQL, and Bootstrap, the system successfully optimizes administration and accelerates data recapitulation. However, mobile responsiveness remains limited. Future development suggests adding automated grading and user interface (UI) enhancements. Keywords: Information System, Incremental Model, PIECES Analysis, Digital Report